Do health halos and conspicuous consumption influence the appeal and risk perceptions of e-cigarettes among young Cambodian men?. Issue 4 (27th January 2021) - Stubbs, Thomas; Thomas, Samantha; Pitt, Hannah; Daube, Mike
Abstract : Introduction: Reduced risk perceptions influence young people's consumption behaviours of e-cigarettes, suggesting that a health halo effect may be associated with these devices. Product, performative, and social factors contribute to the appeal of e-cigarettes, with young people using e-cigarettes with friends as part of social interactions. This study explored the factors that influence the appeal and risk perceptions associated with e-cigarettes among young Cambodian men. Methods: A mixed-method, interviewer-administered survey with 147 young men in Cambodia, who were aged between 18 and 24 years and identified as cigarette smokers. Participants described their attitudes and consumption behaviours surrounding e-cigarettes, recalled e-cigarette promotions, and described their risk perceptions towards e-cigarettes. Descriptive statistics were calculated for quantitative data, and thematic analysis was conducted for qualitative data. Results: Some participants associated e-cigarettes with affluence and exclusivity, describing these devices as products that rich and/or younger people use. Participants also described product attributes that were appealing about e-cigarettes, such as variety of flavours, vapour, and performing smoke 'styles' with friends, which differentiated the product from combustible cigarettes. Participants also had reduced risk perceptions towards e-cigarettes, with some commenting that e-cigarettes were not harmful or might be health-enhancing. Conclusion: Some young people may perceive e-cigarettes as a form of conspicuous consumption, which they associated with social status and identity. A health halo effect appears to be associated with e-cigarettes among some young people. This may influence young people to underestimate the potential health risks associated with these devices.